White matter microstructural alterations in patients with neuropathic pain after spinal cord injury: a diffusion tensor imaging study - Dong Dong; Dong Dong; Koichi Hosomi; Nobuhiko Mori; Yoshi-ichiro Kamijo; Yoshi-ichiro Kamijo; Yohei Furotani; Daisuke Yamagami; Daisuke Yamagami; Yu-ichiro Ohnishi; Yu-ichiro Ohnishi; Yoshiyuki Watanabe; et al. (Frontiers in Neurology, 2023)
BackgroundThrough contrastive analysis, we aimed to identify the white matter brain regions that show microstructural changes in patients with neuropathic pain (NP) after spinal cord injury (SCI).MethodsWe categorized patients with SCI into NP (n = 30) and non-NP (n = 15) groups. We extracted diffusion tensor maps of fractional anisotropy (FA) and mean (MD), axial (AD), and radial (RD) diffusivity. A randomization-based method in tract-based spatial statistics was used to perform voxel-wise group comparisons among the FA, MD, AD, and RD for nonparametric permutation tests.ResultsAtlas-based analysis located significantly different regions (p < 0.05) in the appointed brain atlas. Compared to the non-NP group, the NP group showed higher FA in the posterior body and splenium of the corpus callosum and higher AD in the corpus callosum, internal capsule, corona radiata, posterior thalamic radiation, sagittal stratum, external capsule, cingulum, fornix/stria terminalis, superior longitudinal fasciculus, and uncinate fasciculus.ConclusionThe results demonstrated that compared with the non-NP group, NP pathogenesis after SCI was potentially related to higher values in FA that are associated with microstructural changes in the posterior body and splenium of the corpus callosum, which could be regarded as central sensitization or network hyperexcitability.